Composite material prepared from modified lignin and liquid silicone rubber and application of composite material

By modifying the design of liquid silicone rubber and lignin, destroying the internal hydrogen bonds of lignin and increasing hydrophilic groups, combined with defoaming agent treatment, the problems of poor compatibility and incomplete curing in the preparation of composite materials are solved, and the mechanics is improved and physical properties reduce preparation costs and waste and improve product quality.

CN119177023APending Publication Date: 2024-12-24HANGSHI TECH DEV (HANGZHOU) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411401799.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The prior art cannot effectively destroy the internal hydrogen bonds of lignin, resulting in poor compatibility with liquid silicone rubber, incomplete curing during the preparation of composite materials, high material waste and preparation costs, affecting the aesthetic appearance and physical and chemical properties.

Method used

By designing modified liquid silicone rubber and modified lignin, polydimethylsiloxane and white carbon black surface graft modification is used to combine sodium ion solution to destroy the aryl ether bond and carbon-oxygen bond of lignin, increasing timber The hydrophilic group of the carbon, using defoamers to reduce surface tension, and improve the mechanical and physical properties of the composite material.

Benefits of technology

It improves the compatibility of lignin and liquid silicone rubber, increases the mechanical and physical properties of composite materials, reduces preparation costs and material waste, reduces bubble phenomena, and improves product quality and market competitiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177023A_ABST
    Figure CN119177023A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material prepared from modified lignin and liquid silicone rubber and application of the composite material, and relates to the technical field of rubber. The modified liquid silicone rubber is prepared from the following components in parts by weight: 60 to 90 parts of vinyl-terminated silicone oil, 10 to 30 parts of white carbon black, 2 to 8 parts of end-side hydrogen-containing silicone oil, 5 to 10 parts of polydimethylsiloxane, 2 to 8 parts of hexamethylsiloxane, 1 to 4 parts of tackifier, 0.1 to 0.8 part of platinum catalyst and 20 to 50 parts of dimethyl silicone oil. By designing the modified liquid silicone rubber, the function of destroying hydrogen bonds in the lignin is realized, the problem of poor compatibility of the lignin and the liquid silicone rubber is solved, the mechanical properties of the composite material prepared from the modified lignin and the liquid silicone rubber can be improved, the waste of raw materials is reduced, and the quality and economic benefits of the product are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber, in particular to a composite material prepared from modified lignin and liquid silicone rubber and application thereof. Background Art

[0002] With the advancement of science and technology and the development of society, the composite materials industry has received key support from governments at all levels and national industrial policies in recent years, encouraging the development of R&D innovation and industrial upgrading. Lignin is a natural polymer compound that is widely present in the cell walls of plants and is a by-product of the papermaking industry. Due to the complexity of its structure and composition, the application of lignin is subject to certain restrictions. In order to broaden the application field of lignin, chemical modification methods such as sulfonation, amination, epoxidation, esterification and graft copolymerization are used to improve the performance of lignin, improve its compatibility with the matrix, reduce the size of lignin, reduce the tendency of self-aggregation, improve its dispersibility and performance in composite materials, and improve The industrial utilization value of lignin is of great significance to environmental protection and resource recycling. Liquid silica sol, as a high-performance elastomer, has excellent electrical properties, weather resistance and biocompatibility. It is widely used in electronics, medical and aerospace fields. Compared with mixed semi-solid silicone and common room temperature vulcanized single-component silicone, it has good fluidity and fast vulcanization. It can be cast or injection molded. Liquid silicone rubber is divided into self-adhesive and non-self-adhesive types. It can be cured at room temperature or high temperature. High-temperature curing can be completed within seconds. Research on composite materials prepared by modified lignin and liquid silicone rubber is of great significance to promote the high-value utilization of wood and promote green and sustainable development. The molecular structure of lignin is complex and the bond with rubber is not tight enough, resulting in relatively poor mechanical properties of the composite material and limited processing performance. The mixing and processing process of modified lignin and liquid silicone rubber is relatively complicated, requiring special production equipment and processes. The material is prone to breakage and deformation, affecting the product's yield and good rate. In order to improve the compatibility with rubber, poor interface bonding still exists in actual applications.

[0003] Patent document CN104845375B discloses a low dielectric constant liquid silicone rubber composite material and a preparation method thereof. The above patent realizes the use of inorganic hollow fillers as reinforcing fillers for liquid silicone rubber. Since the dielectric constant of air is only 1, which is much lower than the dielectric constant of the silicone rubber matrix, the use of hollow fillers containing air as reinforcing fillers for liquid silicone rubber can greatly reduce the dielectric constant of the material while ensuring that the silicone rubber has a certain mechanical strength. The obtained low dielectric constant liquid silicone rubber composite material has broad application prospects in the fields of integrated circuits and semiconductor industries, but the above patent cannot achieve the function of destroying the hydrogen bonds inside lignin.

[0004] Patent document CN110408217B discloses a liquid silicone rubber / graphene aerogel highly conductive composite material and a preparation method thereof. The above patent realizes the introduction of graphene aerogel as a filler conductive network on the basis of the traditional two-component addition type liquid silicone rubber preparation, thereby maintaining the excellent properties of the silicone rubber itself. At the same time, combined with the three-dimensional pore structure of the graphene aerogel, the conductive percolation threshold of the silicone rubber is reduced, the technical problem of high filler content is overcome, and the material cost is reduced. However, the above patent cannot achieve the function of increasing the solubility of lignin in the composite material.

[0005] Patent document CN103540139B discloses a liquid silicone rubber for glass fiber composite materials with high electrical performance and a preparation method thereof. The above patent has many advantages such as temperature resistance, corrosion resistance, insulation, and flame retardancy. It can be directly applied or laminated on glass fiber tubes and is used for the protection of power transmission lines and high-temperature oil and steam pipelines in various harsh environments such as high temperature, high pressure, and strong corrosion. However, the above patent cannot achieve the function of green environmental protection.

[0006] Patent document CN116004012B discloses a flexible heat storage phase change composite material and a preparation method thereof. The above patent realizes the use of liquid silicone rubber as a supporting material for loading phase change materials, which has strong plasticity; the composite thermal conductive material enhances the thermal conductivity of silicone rubber and improves the efficiency of heat conduction; the embedded thermal conductive material of the thermal conductive-phase change composite microcapsule shell is in contact with the composite thermal conductive material and the phase change material, and the heat transfer efficiency is high; amino silicone oil improves the compatibility of the composite thermal conductive material and silicone rubber, but the above patent cannot achieve the function of reducing surface tension.

[0007] In summary, the above patents cannot achieve the function of destroying the hydrogen bonds inside lignin, cannot achieve the function of increasing the solubility of lignin in the composite material, cannot achieve the function of being green and environmentally friendly, and cannot achieve the function of reducing surface tension, which leads to the problems of poor compatibility between lignin and liquid silicone rubber, incomplete curing and no curing in the preparation process of the composite material, material waste and high preparation cost, and the appearance of bubbles in the preparation process of the composite material that affects the appearance and reduces the physical and chemical properties; To this end, the present application proposes a composite material prepared from modified lignin and liquid silicone rubber, which can achieve the function of destroying the internal hydrogen bonds of lignin, increasing the solubility of lignin in the composite material, achieving the function of green environmental protection, and reducing the surface tension, and its application. Summary of the invention

[0008] The object of the present invention is to provide a composite material prepared from modified lignin and liquid silicone rubber and its application, so as to solve the technical problems proposed in the above background technology that the function of destroying the hydrogen bonds inside lignin cannot be achieved, the function of increasing the solubility of lignin in the composite material cannot be achieved, the function of green environmental protection cannot be achieved, and the function of reducing surface tension cannot be achieved, resulting in poor compatibility between lignin and liquid silicone rubber, incomplete curing and no curing during the preparation of the composite material, material waste and high preparation cost, and the appearance of bubbles in the preparation of the composite material that affects the appearance and reduces the physical and chemical properties.

[0009] To achieve the above object, the present invention provides the following technical solution: a composite material prepared from modified lignin and liquid silicone rubber and its application, comprising modified lignin and modified liquid silicone rubber, wherein the modified liquid silicone rubber comprises the following components in parts by weight: 60 to 90 parts of vinyl-terminated silicone oil; White carbon black: 10 to 30 parts; End side hydrogenated silicone oil: 2 to 8 parts; Polydimethylsiloxane: 5 to 10 parts; Hexamethylsiloxane: 2 to 8 parts; Thickener: 1 to 4 parts; Platinum catalyst: 0.1 to 0.8 parts; Dimethyl silicone oil: 20 to 50 parts; The tackifier is an epoxy-containing organosilicon tackifier; The silicon-oxygen bond in the molecular structure of the polydimethylsiloxane has low polarity and high flexibility. The polydimethylsiloxane reduces the interaction between lignin molecules through physical isolation and dispersion. Under the action of the platinum catalyst, the polydimethylsiloxane interacts with the lignin. The polydimethylsiloxane and white carbon black are modified by surface grafting, and the polydimethylsiloxane is grafted on the surface of the white carbon black.

[0010] Preferably, the modified lignin comprises the following components in parts by weight: sawdust: 10 to 40 parts; Organic solvent: 30 to 80 parts; Acidifier: 5 to 10 parts; Distilled water: 10 to 15 parts; Acetone solution: 20 to 50 parts; Sodium ion solution: 0.2 to 1.5 parts; The sodium ion solution promotes the dissolution of lignin by providing an alkaline environment, the oxygen-containing groups and aromatic ether bonds in the lignin are destroyed, the methoxy content is reduced, the carbon-oxygen bonds are obviously broken, the carbon-carbon bonds are partially degraded, and unsaturated bonds are generated. During the dissolution process, the lignin undergoes demethoxylation and dehydration reactions, so that the lignin macromolecules are degraded into small and uniform structural units, and the relative molecular weight of the lignin is reduced, but the main structure of the aromatic ring of the lignin remains stable, and more hydrophilic groups, such as sulfonic acid groups, are introduced into the lignin modified by the sodium ion solution.

[0011] Preferably, the hexamethylsiloxane is mixed with water to undergo a hydrolysis reaction, ammonia produced in the hydrolysis reaction is extracted using negative pressure, the treated liquid is mixed with silica, a chemical reaction occurs with hydroxyl groups on the surface of silica, and the organic groups are connected to the surface of silica particles through chemical bonds.

[0012] Preferably, the composite material prepared from the modified lignin and liquid silicone rubber is internally designed with a defoamer, and the defoamer comprises hydrophobic silica, fatty acid ester, deionized water, an emulsifier and a stabilizer.

[0013] Preferably, the preparation process of the modified liquid silicone rubber is: Step 1: Prepare sufficient amounts of vinyl-terminated silicone oil, white carbon black, end-side hydrogen-containing silicone oil, polydimethylsiloxane, hexamethylsiloxane, tackifier, platinum catalyst and dimethyl silicone oil; Step 2: Mix white carbon black with polydimethylsiloxane and hexamethylsiloxane and stir evenly; Step 3: Add vinyl-terminated silicone oil and hydrogen-terminated silicone oil and stir evenly; Step 4: Place the mixture into a double planetary mixer and mix; Step 5: Add viscosity enhancer and platinum catalyst and continue stirring; Step 6: Add polydimethylsiloxane and continue stirring; Step 7: Add dimethyl silicone oil to the prepared modified liquid silicone rubber according to the required concentration; Step 8: After vacuum degassing, store the modified silicone rubber away from light.

[0014] Preferably, the preparation process of the modified lignin is: Step 1: Prepare sufficient sawdust, wash, dry and crush to obtain wood powder for later use; Step 2: Mix the wood powder and the organic solvent and stir thoroughly; Step 3: adding distilled water to the mixture to regenerate cellulose; Step 4: distilling the filtrate after filtration and separation to separate the mixed solution containing lignin; Step 5: adding acetone solution to the mixed solution to precipitate lignin; Step 6: After acid washing and drying the precipitated lignin, lignin is obtained; Step 7: Add sodium ion solution to lignin and perform ion exchange reaction in an environment of 25°C and pH=2; Step 8: Drying the reacted lignin to obtain modified lignin.

[0015] Preferably, the preparation process of the defoamer is: Step 1: Prepare sufficient amounts of hydrophobic silica, fatty acid ester, emulsifier, stabilizer and deionized water; Step 2: Mix hydrophobic silica, fatty acid ester, emulsifier and stabilizer in a weight ratio of 20:3:1:0.2, add to the reaction kettle, and stir evenly; Step 3: Slowly add deionized water and continue stirring for a while to form a stable emulsion; Step 4: removing impurities and unemulsified components from the prepared defoamer by centrifugal separation; Step 5: Conduct quality inspection on the purified defoaming agent.

[0016] Preferably, the preparation process of the composite material prepared from the modified lignin and liquid silicone rubber is: Step 1: Prepare sufficient amount of modified lignin and modified liquid silicone rubber; Step 2: Mix the modified lignin and the modified liquid silicone rubber and stir them thoroughly; Step 4: Add the crosslinking agent and defoaming agent to the mixture and react at 155°C for 1 hour; Step 5: Cover the inner wall of the mold with plastic film and spray the release agent; Step 6: inject the reacted mixture into a mold, and solidify the composite material by heating and pressurizing; Step 7: Clean and cut the demoulded material to obtain the final product.

[0017] Preferably, the application of the modified lignin and the composite material prepared with liquid silicone rubber includes application in tire preparation, and the tire preparation process is: in the process of preparing the composite material, the hardness of the final product is increased by reducing the amount of dimethyl silicone oil, the prepared composite material is added to an internal mixer for internal mixing, the rubber material is pressed into a specific shape by an extruder, the rubber material is processed into semi-finished products of different sizes and shapes, the semi-finished products are obtained by conforming, cutting the steel cord and forming the tire bead, and then combined into a green tire, and steam high-temperature heated by a vulcanizer to increase the performance of the tire, and the prepared tire is quality tested.

[0018] Preferably, the application of the composite material prepared from the modified lignin and liquid silicone rubber also includes application in the preparation of pacifiers. The preparation process of the pacifier is as follows: in the process of preparing the composite material, the hardness of the final product is reduced by increasing the amount of dimethyl silicone oil, the prepared composite material is injected into a hot runner mold, and a curing reaction occurs at a mold temperature of 170 to 200°C to form the final shape of the pacifier, and the pacifier is obtained after cooling and demolding. The prepared pacifier needs to undergo appearance inspection and functional testing.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention achieves the function of destroying the hydrogen bonds inside lignin by designing a modified liquid silicone rubber, solves the problem of poor compatibility between lignin and liquid silicone rubber, can increase the mechanical properties of the composite material prepared from the modified lignin and liquid silicone rubber, reduces the waste of raw materials, and improves the quality and economic benefits of the product; 2. The present invention realizes the function of increasing the solubility of lignin in the composite material by designing modified lignin, solves the problem of incomplete curing and no curing in the preparation process of the composite material, can increase the physical properties and use effect of the composite material, reduce the phenomenon of stratification and surface bubbles in the composite material, and increase the reliability of the composite material; 3. The present invention realizes the function of green environmental protection by designing an organic solvent, solves the problems of material waste and high preparation cost, can reduce the production cost, reduce the pollution and damage to the environment, and improve the economic benefits of the product; 4. The present invention achieves the function of reducing surface tension by designing a defoaming agent, solves the problem of bubbles affecting the appearance and reducing the physical and chemical properties during the preparation of the composite material, shortens the production cycle, increases the market competitiveness of the product, improves the quality of the product, and increases the use value and life of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of the preparation process of the modified liquid silicone rubber of the present invention; Figure 2 This is a schematic diagram of the preparation process of modified lignin of the present invention; Figure 3 It is a schematic diagram of the preparation process of the defoamer of the present invention; Figure 4 It is a schematic diagram of the preparation process of the composite material of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0022] See also Figure 1 , Figure 2 , Figure 3 and Figure 4 , a composite material prepared from modified lignin and liquid silicone rubber, comprising modified lignin and modified liquid silicone rubber, wherein the modified liquid silicone rubber comprises the following components in parts by weight: 70 parts of vinyl-terminated silicone oil; White carbon black: 25 parts; End side hydrogenated silicone oil: 5 parts; Polydimethylsiloxane: 6 parts; Hexamethylsiloxane: 4 parts; Thickener: 2 parts; Platinum catalyst: 0.6 parts; Dimethyl silicone oil: 35 parts; The tackifier is an epoxy-containing organosilicon tackifier; The silicon-oxygen bond in the molecular structure of the polydimethylsiloxane has low polarity and high flexibility. The polydimethylsiloxane reduces the interaction between lignin molecules through physical isolation and dispersion. Under the action of the platinum catalyst, the polydimethylsiloxane interacts with the lignin. The polydimethylsiloxane and white carbon black are modified by surface grafting, and polydimethylsiloxane is grafted on the surface of white carbon black to change the polarity of the surface of white carbon black particles and improve the dispersibility of white carbon black itself; The modified lignin comprises the following components in parts by weight: sawdust: 20 parts; Organic solvent: 50 parts; Acidifier: 6 parts; Distilled water: 12 parts; Acetone solution: 35 parts; Sodium ion solution: 0.8 parts; The sodium ion solution promotes the dissolution of lignin by providing an alkaline environment, the oxygen-containing groups and aromatic ether bonds in the lignin are destroyed, the methoxy content is reduced, the carbon-oxygen bonds are significantly broken, the carbon-carbon bonds are partially degraded, and unsaturated bonds are generated. During the dissolution process, the lignin undergoes demethoxylation and dehydration reactions, so that the lignin macromolecules are degraded into small and uniform structural units, and the relative molecular weight of the lignin is reduced, but the main structure of the aromatic ring of the lignin remains stable, and more hydrophilic groups, such as sulfonic acid groups, are introduced into the lignin modified by the sodium ion solution; The hexamethylsiloxane is mixed with water to undergo a hydrolysis reaction, and ammonia produced in the hydrolysis reaction is extracted using negative pressure. The treated liquid is mixed with silica, and a chemical reaction occurs with hydroxyl groups on the surface of silica, thereby connecting the organic groups to the surface of silica particles through chemical bonds.

[0023] The composite material prepared by the modified lignin and liquid silicone rubber is designed with a defoamer inside, and the defoamer includes hydrophobic silicon dioxide, fatty acid ester, deionized water, an emulsifier and a stabilizer; Further, prepare components by weight of 70 parts of vinyl-terminated silicone oil, 25 parts of white carbon black, 5 parts of end-side hydrogenated silicone oil, 6 parts of polydimethylsiloxane, 4 parts of hexamethylsiloxane, 2 parts of tackifier, 0.6 parts of platinum catalyst and 35 parts of dimethyl silicone oil, mix the white carbon black with the polydimethylsiloxane and the hexamethylsiloxane, stir evenly, add the vinyl-terminated silicone oil and the end-side hydrogenated silicone oil and stir evenly, put the mixture into a double planetary mixer and mix and stir, add the tackifier and the platinum catalyst, continue stirring, add polydimethylsiloxane, continue stirring, add 20 parts of dimethyl silicone oil to the prepared modified liquid silicone rubber, and store the modified silicone rubber in the dark after vacuum degassing; Prepare components in parts by weight of 20 parts of sawdust, 50 parts of organic solvent, 6 parts of acidulant, 12 parts of distilled water, 35 parts of acetone solution and 0.8 parts of sodium ion solution, wash, dry and crush the sawdust to obtain wood powder for later use, mix the wood powder with the organic solvent, stir thoroughly, add distilled water to the mixture to regenerate cellulose, distill the filtrate after filtration and separation to separate a mixed solution containing lignin, add acetone solution to the mixed solution to precipitate lignin, acid wash and dry the precipitated lignin to obtain lignin, add sodium ion solution to the lignin, perform ion exchange reaction in an environment of 25° C. and pH=2, dry the lignin after the reaction to obtain modified lignin; Prepare sufficient amounts of hydrophobic silica, fatty acid ester, emulsifier, stabilizer and deionized water, and mix the hydrophobic silica, fatty acid ester, emulsifier and stabilizer in a weight ratio of 20:3:1:0.2, add them to a reactor, stir evenly, slowly add deionized water, continue stirring for a period of time to form a stable emulsion, remove impurities and unemulsified components in the prepared defoamer by centrifugal separation, and perform quality inspection on the purified defoamer; Prepare sufficient amounts of modified lignin and modified liquid silicone rubber, mix the modified lignin and modified liquid silicone rubber, stir fully, add a cross-linking agent and a defoaming agent to the mixture, react at 155°C for 1 hour, cover the inner wall of the mold with a plastic film, spray a release agent, inject the reacted mixture into the mold, cure the composite material by heating and pressurizing, and clean and cut the demolded material to obtain the final product. Example 2

[0024] See also Figure 1 , Figure 2 , Figure 3 and Figure 4 , a composite material prepared from modified lignin and liquid silicone rubber, comprising modified lignin and modified liquid silicone rubber, wherein the modified liquid silicone rubber comprises the following components in parts by weight: 70 parts of vinyl-terminated silicone oil; White carbon black: 25 parts; End side hydrogenated silicone oil: 5 parts; Polydimethylsiloxane: 6 parts; Hexamethylsiloxane: 4 parts; Thickener: 2 parts; Platinum catalyst: 0.6 parts; Dimethyl silicone oil: 35 parts; The tackifier is an epoxy-containing organosilicon tackifier; The silicon-oxygen bond in the molecular structure of the polydimethylsiloxane has low polarity and high flexibility. The polydimethylsiloxane reduces the interaction between lignin molecules through physical isolation and dispersion. Under the action of the platinum catalyst, the polydimethylsiloxane interacts with the lignin. The polydimethylsiloxane and white carbon black are modified by surface grafting, and polydimethylsiloxane is grafted on the surface of white carbon black to change the polarity of the surface of white carbon black particles and improve the dispersibility of white carbon black itself; The modified lignin comprises the following components in parts by weight: sawdust: 20 parts; Organic solvent: 50 parts; Acidifier: 6 parts; Distilled water: 12 parts; Acetone solution: 35 parts; Sodium ion solution: 0.8 parts; The sodium ion solution promotes the dissolution of lignin by providing an alkaline environment, the oxygen-containing groups and aromatic ether bonds in the lignin are destroyed, the methoxy content is reduced, the carbon-oxygen bonds are significantly broken, the carbon-carbon bonds are partially degraded, and unsaturated bonds are generated. During the dissolution process, the lignin undergoes demethoxylation and dehydration reactions, so that the lignin macromolecules are degraded into small and uniform structural units, and the relative molecular weight of the lignin is reduced, but the main structure of the aromatic ring of the lignin remains stable, and more hydrophilic groups, such as sulfonic acid groups, are introduced into the lignin modified by the sodium ion solution; The hexamethylsiloxane is mixed with water to undergo a hydrolysis reaction, and ammonia produced in the hydrolysis reaction is extracted using negative pressure. The treated liquid is mixed with silica, and a chemical reaction occurs with hydroxyl groups on the surface of silica, thereby connecting the organic groups to the surface of silica particles through chemical bonds.

[0025] The composite material prepared by the modified lignin and liquid silicone rubber is designed with a defoamer inside, and the defoamer includes hydrophobic silicon dioxide, fatty acid ester, deionized water, an emulsifier and a stabilizer; Further, prepare components by weight of 70 parts of vinyl-terminated silicone oil, 25 parts of white carbon black, 5 parts of end-side hydrogenated silicone oil, 6 parts of polydimethylsiloxane, 4 parts of hexamethylsiloxane, 2 parts of tackifier, 0.6 parts of platinum catalyst and 35 parts of dimethyl silicone oil, mix the white carbon black with the polydimethylsiloxane and the hexamethylsiloxane, stir evenly, add the vinyl-terminated silicone oil and the end-side hydrogenated silicone oil and stir evenly, put the mixture into a double planetary mixer and mix and stir, add the tackifier and the platinum catalyst, continue stirring, add polydimethylsiloxane, continue stirring, add 30 parts of dimethyl silicone oil to the prepared modified liquid silicone rubber, and store the modified silicone rubber in the dark after vacuum degassing; Prepare components in parts by weight of 20 parts of sawdust, 50 parts of organic solvent, 6 parts of acidulant, 12 parts of distilled water, 35 parts of acetone solution and 0.8 parts of sodium ion solution, wash, dry and crush the sawdust to obtain wood powder for later use, mix the wood powder with the organic solvent, stir thoroughly, add distilled water to the mixture to regenerate cellulose, distill the filtrate after filtration and separation to separate a mixed solution containing lignin, add acetone solution to the mixed solution to precipitate lignin, acid wash and dry the precipitated lignin to obtain lignin, add sodium ion solution to the lignin, perform ion exchange reaction in an environment of 25° C. and pH=2, dry the lignin after the reaction to obtain modified lignin; Prepare sufficient amounts of hydrophobic silica, fatty acid ester, emulsifier, stabilizer and deionized water, and mix the hydrophobic silica, fatty acid ester, emulsifier and stabilizer in a weight ratio of 20:3:1:0.2, add them to a reactor, stir evenly, slowly add deionized water, continue stirring for a period of time to form a stable emulsion, remove impurities and unemulsified components in the prepared defoamer by centrifugal separation, and perform quality inspection on the purified defoamer; Prepare sufficient amounts of modified lignin and modified liquid silicone rubber, mix the modified lignin and modified liquid silicone rubber, stir fully, add a cross-linking agent and a defoaming agent to the mixture, react at 155°C for 1 hour, cover the inner wall of the mold with a plastic film, spray a release agent, inject the reacted mixture into the mold, cure the composite material by heating and pressurizing, and clean and cut the demolded material to obtain the final product. Example 3

[0026] See also Figure 1 , Figure 2 , Figure 3 and Figure 4, a composite material prepared from modified lignin and liquid silicone rubber, comprising modified lignin and modified liquid silicone rubber, wherein the modified liquid silicone rubber comprises the following components in parts by weight: 70 parts of vinyl-terminated silicone oil; White carbon black: 25 parts; End side hydrogenated silicone oil: 5 parts; Polydimethylsiloxane: 6 parts; Hexamethylsiloxane: 4 parts; Thickener: 2 parts; Platinum catalyst: 0.6 parts; Dimethyl silicone oil: 35 parts; The tackifier is an epoxy-containing organosilicon tackifier; The silicon-oxygen bond in the molecular structure of the polydimethylsiloxane has low polarity and high flexibility. The polydimethylsiloxane reduces the interaction between lignin molecules through physical isolation and dispersion. Under the action of the platinum catalyst, the polydimethylsiloxane interacts with the lignin. The polydimethylsiloxane and white carbon black are modified by surface grafting, and polydimethylsiloxane is grafted on the surface of white carbon black to change the polarity of the surface of white carbon black particles and improve the dispersibility of white carbon black itself; The modified lignin comprises the following components in parts by weight: sawdust: 20 parts; Organic solvent: 50 parts; Acidifier: 6 parts; Distilled water: 12 parts; Acetone solution: 35 parts; Sodium ion solution: 0.8 parts; The sodium ion solution promotes the dissolution of lignin by providing an alkaline environment, the oxygen-containing groups and aromatic ether bonds in the lignin are destroyed, the methoxy content is reduced, the carbon-oxygen bonds are significantly broken, the carbon-carbon bonds are partially degraded, and unsaturated bonds are generated. During the dissolution process, the lignin undergoes demethoxylation and dehydration reactions, so that the lignin macromolecules are degraded into small and uniform structural units, and the relative molecular weight of the lignin is reduced, but the main structure of the aromatic ring of the lignin remains stable, and more hydrophilic groups, such as sulfonic acid groups, are introduced into the lignin modified by the sodium ion solution; The hexamethylsiloxane is mixed with water to undergo a hydrolysis reaction, and ammonia produced in the hydrolysis reaction is extracted using negative pressure. The treated liquid is mixed with silica, and a chemical reaction occurs with hydroxyl groups on the surface of silica, thereby connecting the organic groups to the surface of silica particles through chemical bonds.

[0027] The composite material prepared by the modified lignin and liquid silicone rubber is designed with a defoamer inside, and the defoamer includes hydrophobic silicon dioxide, fatty acid ester, deionized water, an emulsifier and a stabilizer; Further, prepare components by weight of 70 parts of vinyl-terminated silicone oil, 25 parts of white carbon black, 5 parts of end-side hydrogenated silicone oil, 6 parts of polydimethylsiloxane, 4 parts of hexamethylsiloxane, 2 parts of tackifier, 0.6 parts of platinum catalyst and 35 parts of dimethyl silicone oil, mix the white carbon black with the polydimethylsiloxane and the hexamethylsiloxane, stir evenly, add the vinyl-terminated silicone oil and the end-side hydrogenated silicone oil and stir evenly, put the mixture into a double planetary mixer and mix and stir, add the tackifier and the platinum catalyst, continue stirring, add polydimethylsiloxane, continue stirring, add 40 parts of dimethyl silicone oil to the prepared modified liquid silicone rubber, and store the modified silicone rubber in the dark after vacuum degassing; Prepare components in parts by weight of 20 parts of sawdust, 50 parts of organic solvent, 6 parts of acidulant, 12 parts of distilled water, 35 parts of acetone solution and 0.8 parts of sodium ion solution, wash, dry and crush the sawdust to obtain wood powder for later use, mix the wood powder with the organic solvent, stir thoroughly, add distilled water to the mixture to regenerate cellulose, distill the filtrate after filtration and separation to separate a mixed solution containing lignin, add acetone solution to the mixed solution to precipitate lignin, acid wash and dry the precipitated lignin to obtain lignin, add sodium ion solution to the lignin, perform ion exchange reaction in an environment of 25° C. and pH=2, dry the lignin after the reaction to obtain modified lignin; Prepare sufficient amounts of hydrophobic silica, fatty acid ester, emulsifier, stabilizer and deionized water, and mix the hydrophobic silica, fatty acid ester, emulsifier and stabilizer in a weight ratio of 20:3:1:0.2, add them to a reactor, stir evenly, slowly add deionized water, continue stirring for a period of time to form a stable emulsion, remove impurities and unemulsified components in the prepared defoamer by centrifugal separation, and perform quality inspection on the purified defoamer; Prepare sufficient amounts of modified lignin and modified liquid silicone rubber, mix the modified lignin and modified liquid silicone rubber, stir fully, add a cross-linking agent and a defoaming agent to the mixture, react at 155°C for 1 hour, cover the inner wall of the mold with a plastic film, spray a release agent, inject the reacted mixture into the mold, cure the composite material by heating and pressurizing, and clean and cut the demolded material to obtain the final product. Example 4

[0028] See also Figure 1 , Figure 2 , Figure 3 and Figure 4 , a composite material prepared from modified lignin and liquid silicone rubber, comprising modified lignin and modified liquid silicone rubber, wherein the modified liquid silicone rubber comprises the following components in parts by weight: 70 parts of vinyl-terminated silicone oil; White carbon black: 25 parts; End side hydrogenated silicone oil: 5 parts; Polydimethylsiloxane: 6 parts; Hexamethylsiloxane: 4 parts; Thickener: 2 parts; Platinum catalyst: 0.6 parts; Dimethyl silicone oil: 35 parts; The tackifier is an epoxy-containing organosilicon tackifier; The silicon-oxygen bond in the molecular structure of the polydimethylsiloxane has low polarity and high flexibility. The polydimethylsiloxane reduces the interaction between lignin molecules through physical isolation and dispersion. Under the action of the platinum catalyst, the polydimethylsiloxane interacts with the lignin. The polydimethylsiloxane and white carbon black are modified by surface grafting, and polydimethylsiloxane is grafted on the surface of white carbon black to change the polarity of the surface of white carbon black particles and improve the dispersibility of white carbon black itself; The modified lignin comprises the following components in parts by weight: sawdust: 20 parts; Organic solvent: 50 parts; Acidifier: 6 parts; Distilled water: 12 parts; Acetone solution: 35 parts; Sodium ion solution: 0.8 parts; The sodium ion solution promotes the dissolution of lignin by providing an alkaline environment, the oxygen-containing groups and aromatic ether bonds in the lignin are destroyed, the methoxy content is reduced, the carbon-oxygen bonds are significantly broken, the carbon-carbon bonds are partially degraded, and unsaturated bonds are generated. During the dissolution process, the lignin undergoes demethoxylation and dehydration reactions, so that the lignin macromolecules are degraded into small and uniform structural units, and the relative molecular weight of the lignin is reduced, but the main structure of the aromatic ring of the lignin remains stable, and more hydrophilic groups, such as sulfonic acid groups, are introduced into the lignin modified by the sodium ion solution; The hexamethylsiloxane is mixed with water to undergo a hydrolysis reaction, and ammonia produced in the hydrolysis reaction is extracted using negative pressure. The treated liquid is mixed with silica, and a chemical reaction occurs with hydroxyl groups on the surface of silica, thereby connecting the organic groups to the surface of silica particles through chemical bonds.

[0029] The composite material prepared by the modified lignin and liquid silicone rubber is designed with a defoamer inside, and the defoamer includes hydrophobic silicon dioxide, fatty acid ester, deionized water, an emulsifier and a stabilizer; Further, prepare components by weight of 70 parts of vinyl-terminated silicone oil, 25 parts of white carbon black, 5 parts of end-side hydrogenated silicone oil, 6 parts of polydimethylsiloxane, 4 parts of hexamethylsiloxane, 2 parts of tackifier, 0.6 parts of platinum catalyst and 35 parts of dimethyl silicone oil, mix the white carbon black with the polydimethylsiloxane and the hexamethylsiloxane, stir evenly, add the vinyl-terminated silicone oil and the end-side hydrogenated silicone oil and stir evenly, put the mixture into a double planetary mixer and mix and stir, add the tackifier and the platinum catalyst, continue stirring, add polydimethylsiloxane, continue stirring, add 50 parts of dimethyl silicone oil to the prepared modified liquid silicone rubber, and store the modified silicone rubber in the dark after vacuum degassing; Prepare components in parts by weight of 20 parts of sawdust, 50 parts of organic solvent, 6 parts of acidulant, 12 parts of distilled water, 35 parts of acetone solution and 0.8 parts of sodium ion solution, wash, dry and crush the sawdust to obtain wood powder for later use, mix the wood powder with the organic solvent, stir thoroughly, add distilled water to the mixture to regenerate cellulose, distill the filtrate after filtration and separation to separate a mixed solution containing lignin, add acetone solution to the mixed solution to precipitate lignin, acid wash and dry the precipitated lignin to obtain lignin, add sodium ion solution to the lignin, perform ion exchange reaction in an environment of 25° C. and pH=2, dry the lignin after the reaction to obtain modified lignin; Prepare sufficient amounts of hydrophobic silica, fatty acid ester, emulsifier, stabilizer and deionized water, and mix the hydrophobic silica, fatty acid ester, emulsifier and stabilizer in a weight ratio of 20:3:1:0.2, add them to a reactor, stir evenly, slowly add deionized water, continue stirring for a period of time to form a stable emulsion, remove impurities and unemulsified components in the prepared defoamer by centrifugal separation, and perform quality inspection on the purified defoamer; Prepare sufficient amounts of modified lignin and modified liquid silicone rubber, mix the modified lignin and modified liquid silicone rubber, stir fully, add a cross-linking agent and a defoaming agent to the mixture, react at 155°C for 1 hour, cover the inner wall of the mold with a plastic film, spray a release agent, inject the reacted mixture into the mold, cure the composite material by heating and pressurizing, and clean and cut the demolded material to obtain the final product. Example 5

[0030] See also Figure 1 , Figure 2 , Figure 3 and Figure 4 , a composite material prepared from modified lignin and liquid silicone rubber, comprising modified lignin and modified liquid silicone rubber, wherein the modified liquid silicone rubber comprises the following components in parts by weight: 70 parts of vinyl-terminated silicone oil; White carbon black: 25 parts; End side hydrogenated silicone oil: 5 parts; Polydimethylsiloxane: 6 parts; Hexamethylsiloxane: 4 parts; Thickener: 2 parts; Platinum catalyst: 0.6 parts; Dimethyl silicone oil: 35 parts; The tackifier is an epoxy-containing organosilicon tackifier; The silicon-oxygen bond in the molecular structure of the polydimethylsiloxane has low polarity and high flexibility. The polydimethylsiloxane reduces the interaction between lignin molecules through physical isolation and dispersion. Under the action of the platinum catalyst, the polydimethylsiloxane interacts with the lignin. The polydimethylsiloxane and white carbon black are modified by surface grafting, and polydimethylsiloxane is grafted on the surface of white carbon black to change the polarity of the surface of white carbon black particles and improve the dispersibility of white carbon black itself; The modified lignin comprises the following components in parts by weight: sawdust: 20 parts; Organic solvent: 50 parts; Acidifier: 6 parts; Distilled water: 12 parts; Acetone solution: 35 parts; Sodium ion solution: 0.8 parts; The sodium ion solution promotes the dissolution of lignin by providing an alkaline environment, the oxygen-containing groups and aromatic ether bonds in the lignin are destroyed, the methoxy content is reduced, the carbon-oxygen bonds are significantly broken, the carbon-carbon bonds are partially degraded, and unsaturated bonds are generated. During the dissolution process, the lignin undergoes demethoxylation and dehydration reactions, so that the lignin macromolecules are degraded into small and uniform structural units, and the relative molecular weight of the lignin is reduced, but the main structure of the aromatic ring of the lignin remains stable, and more hydrophilic groups, such as sulfonic acid groups, are introduced into the lignin modified by the sodium ion solution; The hexamethylsiloxane is mixed with water to undergo a hydrolysis reaction, and ammonia produced in the hydrolysis reaction is extracted using negative pressure. The treated liquid is mixed with silica, and a chemical reaction occurs with hydroxyl groups on the surface of silica, thereby connecting the organic groups to the surface of silica particles through chemical bonds.

[0031] The composite material prepared by the modified lignin and liquid silicone rubber is designed with a defoamer inside, and the defoamer includes hydrophobic silicon dioxide, fatty acid ester, deionized water, an emulsifier and a stabilizer; Further, prepare components by weight of 70 parts of vinyl-terminated silicone oil, 25 parts of white carbon black, 5 parts of end-side hydrogenated silicone oil, 6 parts of polydimethylsiloxane, 4 parts of hexamethylsiloxane, 2 parts of tackifier, 0.6 parts of platinum catalyst and 35 parts of dimethyl silicone oil, mix the white carbon black with the polydimethylsiloxane and the hexamethylsiloxane, stir evenly, add the vinyl-terminated silicone oil and the end-side hydrogenated silicone oil and stir evenly, put the mixture into a double planetary mixer for mixing and stirring, add the tackifier and the platinum catalyst, continue stirring, add polydimethylsiloxane, continue stirring, perform vacuum degassing on the modified silicone rubber and store it away from light; Prepare components in parts by weight of 20 parts of sawdust, 50 parts of organic solvent, 6 parts of acidulant, 12 parts of distilled water, 35 parts of acetone solution and 0.8 parts of sodium ion solution, wash, dry and crush the sawdust to obtain wood powder for later use, mix the wood powder with the organic solvent, stir thoroughly, add distilled water to the mixture to regenerate cellulose, distill the filtrate after filtration and separation to separate a mixed solution containing lignin, add acetone solution to the mixed solution to precipitate lignin, acid wash and dry the precipitated lignin to obtain lignin, add sodium ion solution to the lignin, perform ion exchange reaction in an environment of 25° C. and pH=2, dry the lignin after the reaction to obtain modified lignin; Prepare sufficient amounts of hydrophobic silica, fatty acid ester, emulsifier, stabilizer and deionized water, and mix the hydrophobic silica, fatty acid ester, emulsifier and stabilizer in a weight ratio of 20:3:1:0.2, add them to a reactor, stir evenly, slowly add deionized water, continue stirring for a period of time to form a stable emulsion, remove impurities and unemulsified components in the prepared defoamer by centrifugal separation, and perform quality inspection on the purified defoamer; Prepare sufficient amounts of modified lignin and modified liquid silicone rubber, mix the modified lignin and modified liquid silicone rubber, stir fully, add a cross-linking agent and a defoaming agent to the mixture, react at 155°C for 1 hour, cover the inner wall of the mold with a plastic film, spray a release agent, inject the reacted mixture into the mold, cure the composite material by heating and pressurizing, and clean and cut the demolded material to obtain the final product.

[0032] Performance Testing The composite materials prepared in Examples 1-5 were tested for tensile strength, elongation at break, and density. The test methods are as follows: Tensile strength and elongation at break are tested according to GB / T528-2009; Density is tested according to GB / T6343-2009;

[0033] Working principle: prepare 0 to 90 parts of vinyl-terminated silicone oil, 10 to 30 parts of white carbon black, 2 to 8 parts of end-side hydrogen-containing silicone oil, 5 to 10 parts of polydimethylsiloxane, 2 to 8 parts of hexamethylsiloxane, 1 to 4 parts of tackifier, 0.1 to 0.8 parts of platinum catalyst and 20 to 50 parts of dimethyl silicone oil, mix the white carbon black with polydimethylsiloxane and hexamethylsiloxane, stir evenly, add the vinyl-terminated silicone oil and the end-side hydrogen-containing silicone oil and stir evenly, put the mixture into a double planetary mixer for mixing and stirring, add the tackifier and the platinum catalyst, continue stirring, add polydimethylsiloxane, continue stirring, perform vacuum degassing on the modified silicone rubber and store it away from light; 10 to 40 parts of sawdust, 30 to 80 parts of organic solvent, 5 to 10 parts of acidulant, 10 to 15 parts of distilled water, 20 to 50 parts of acetone solution and 0.2 to 1.5 parts of sodium ion solution are prepared, the sawdust is washed, dried and crushed to obtain wood powder for later use, the wood powder is mixed with the organic solvent, fully stirred, distilled water is added to the mixture to regenerate cellulose, the filtrate after filtration and separation is distilled to separate a mixed solution containing lignin, an acetone solution is added to the mixed solution to precipitate lignin, the precipitated lignin is acid-washed and dried to obtain lignin, a sodium ion solution is added to the lignin, an ion exchange reaction is carried out in an environment of 25° C. and pH=2, and the lignin after the reaction is dried to obtain modified lignin; Prepare sufficient amounts of hydrophobic silica, fatty acid ester, emulsifier, stabilizer and deionized water, and mix the hydrophobic silica, fatty acid ester, emulsifier and stabilizer in a weight ratio of 20:3:1:0.2, add them to a reactor, stir evenly, slowly add deionized water, continue stirring for a period of time to form a stable emulsion, remove impurities and unemulsified components in the prepared defoamer by centrifugal separation, and perform quality inspection on the purified defoamer; Prepare sufficient amounts of modified lignin and modified liquid silicone rubber, mix the modified lignin and modified liquid silicone rubber, stir fully, add a cross-linking agent and a defoaming agent to the mixture, react at 155°C for 1 hour, cover the inner wall of the mold with a plastic film, spray a release agent, inject the reacted mixture into the mold, cure the composite material by heating and pressurizing, and clean and cut the demolded material to obtain the final product.

[0034] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A composite material prepared from modified lignin and liquid silicone rubber, characterized in that: The invention comprises modified lignin and modified liquid silicone rubber, wherein the modified liquid silicone rubber comprises the following components by weight: 60 to 90 parts of vinyl-terminated silicone oil; White carbon black: 10 to 30 parts; End side hydrogenated silicone oil: 2 to 8 parts; Polydimethylsiloxane: 5 to 10 parts; Hexamethylsiloxane: 2 to 8 parts; Thickener: 1 to 4 parts; Platinum catalyst: 0.1 to 0.8 parts; Dimethyl silicone oil: 20 to 50 parts; The tackifier is an epoxy-containing organosilicon tackifier; The silicon-oxygen bond in the molecular structure of the polydimethylsiloxane has low polarity and high flexibility. The polydimethylsiloxane reduces the interaction between lignin molecules through physical isolation and dispersion. Under the action of the platinum catalyst, the polydimethylsiloxane interacts with the lignin. The polydimethylsiloxane and white carbon black are modified by surface grafting, and the polydimethylsiloxane is grafted on the surface of the white carbon black.

2. The composite material prepared from modified lignin and liquid silicone rubber according to claim 1, characterized in that: The modified lignin comprises the following components in parts by weight: sawdust: 10 to 40 parts; Organic solvent: 30 to 80 parts; Acidifier: 5 to 10 parts; Distilled water: 10 to 15 parts; Acetone solution: 20 to 50 parts; Sodium ion solution: 0.2 to 1.5 parts; The sodium ion solution promotes the dissolution of lignin by providing an alkaline environment, the oxygen-containing groups and aromatic ether bonds in the lignin are destroyed, the methoxy content is reduced, the carbon-oxygen bonds are obviously broken, the carbon-carbon bonds are partially degraded, and unsaturated bonds are generated. During the dissolution process, the lignin undergoes demethoxylation and dehydration reactions, so that the lignin macromolecules are degraded into small and uniform structural units, and the relative molecular weight of the lignin is reduced, but the main structure of the aromatic ring of the lignin remains stable, and more hydrophilic groups, such as sulfonic acid groups, are introduced into the lignin modified by the sodium ion solution.

3. The composite material prepared from modified lignin and liquid silicone rubber according to claim 1, characterized in that: The hexamethylsiloxane is mixed with water to undergo a hydrolysis reaction, and ammonia produced in the hydrolysis reaction is extracted using negative pressure. The treated liquid is mixed with silica, and chemically reacts with hydroxyl groups on the surface of silica, thereby connecting the organic groups to the surface of silica particles through chemical bonds.

4. The composite material prepared from modified lignin and liquid silicone rubber according to claim 1, characterized in that: The composite material prepared from the modified lignin and liquid silicone rubber is internally designed with a defoamer, which comprises hydrophobic silicon dioxide, fatty acid ester, deionized water, an emulsifier and a stabilizer.

5. The composite material prepared from modified lignin and liquid silicone rubber according to claim 1, characterized in that: The preparation process of the modified liquid silicone rubber is: Step 1: Prepare sufficient amounts of vinyl-terminated silicone oil, white carbon black, end-side hydrogen-containing silicone oil, polydimethylsiloxane, hexamethylsiloxane, tackifier, platinum catalyst and dimethyl silicone oil; Step 2: Mix white carbon black with polydimethylsiloxane and hexamethylsiloxane and stir evenly; Step 3: Add vinyl-terminated silicone oil and hydrogen-terminated silicone oil and stir evenly; Step 4: Place the mixture into a double planetary mixer and mix; Step 5: Add viscosity enhancer and platinum catalyst and continue stirring; Step 6: Add polydimethylsiloxane and continue stirring; Step 7: Add dimethyl silicone oil to the prepared modified liquid silicone rubber according to the required concentration; Step 8: After vacuum degassing, store the modified silicone rubber away from light.

6. The composite material prepared from modified lignin and liquid silicone rubber according to claim 2, characterized in that: The preparation process of the modified lignin is as follows: Step 1: Prepare sufficient sawdust, wash, dry and crush to obtain wood powder for later use; Step 2: Mix the wood powder and the organic solvent and stir thoroughly; Step 3: adding distilled water to the mixture to regenerate cellulose; Step 4: distilling the filtrate after filtration and separation to separate the mixed solution containing lignin; Step 5: adding acetone solution to the mixed solution to precipitate lignin; Step 6: After acid washing and drying the precipitated lignin, lignin is obtained; Step 7: Add sodium ion solution to lignin and perform ion exchange reaction in an environment of 25°C and pH=2; Step 8: Drying the reacted lignin to obtain modified lignin.

7. The composite material prepared from modified lignin and liquid silicone rubber according to claim 4, characterized in that: The preparation process of the defoamer is: Step 1: Prepare sufficient amounts of hydrophobic silica, fatty acid ester, emulsifier, stabilizer and deionized water; Step 2: Mix hydrophobic silica, fatty acid ester, emulsifier and stabilizer in a weight ratio of 20:3:1:0.2, add to the reaction kettle, and stir evenly; Step 3: Slowly add deionized water and continue stirring for a while to form a stable emulsion; Step 4: removing impurities and unemulsified components from the prepared defoamer by centrifugal separation; Step 5: Conduct quality inspection on the purified defoaming agent.

8. The composite material prepared from modified lignin and liquid silicone rubber according to claim 1, characterized in that: The preparation process of the composite material prepared from the modified lignin and liquid silicone rubber is as follows: Step 1: Prepare sufficient amount of modified lignin and modified liquid silicone rubber; Step 2: Mix the modified lignin and the modified liquid silicone rubber and stir them thoroughly; Step 4: Add the crosslinking agent and defoaming agent to the mixture and react at 155°C for 1 hour; Step 5: Cover the inner wall of the mold with plastic film and spray the release agent; Step 6: inject the reacted mixture into a mold, and solidify the composite material by heating and pressurizing; Step 7: Clean and cut the demoulded material to obtain the final product.

9. An application of a composite material prepared from modified lignin and liquid silicone rubber, applicable to a composite material prepared from modified lignin and liquid silicone rubber according to any one of claims 1 to 8, characterized in that: The application of the modified lignin and the composite material prepared with liquid silicone rubber includes application in tire preparation. The tire preparation process is: in the process of preparing the composite material, the hardness of the final product is increased by reducing the amount of dimethyl silicone oil, the prepared composite material is added to an internal mixer for internal mixing, the rubber material is pressed into a specific shape by an extruder, the rubber material is processed into semi-finished products of different sizes and shapes, the semi-finished products are obtained by conforming, cutting the steel cord and forming the tire bead, and then combined into a green tire, and high-temperature steam heating is performed in a vulcanizer to increase the performance of the tire, and the prepared tire is quality tested.

10. The use of a composite material prepared from modified lignin and liquid silicone rubber according to claim 9, characterized in that: The application of the composite material prepared by the modified lignin and liquid silicone rubber also includes application in the preparation of pacifiers. The preparation process of the pacifier is as follows: in the process of preparing the composite material, the hardness of the final product is reduced by increasing the amount of dimethyl silicone oil, the prepared composite material is injected into a hot runner mold, and a curing reaction occurs at a mold temperature of 170 to 200°C to form the final shape of the pacifier, and the pacifier is obtained after cooling and demolding. The prepared pacifier needs to undergo appearance inspection and functional testing.

Citation Information

Patent Citations

  • A kind of liquid silicone rubber for glass fiber composite material with high electrical performance and preparation method thereof

    CN103540139B

  • A low dielectric constant liquid silicone rubber composite material and its preparation method

    CN104845375B

  • A liquid silicone rubber / graphene aerogel high conductivity composite material and its preparation method

    CN110408217B

  • A flexible heat storage phase change composite material and preparation method thereof

    CN116004012B